Food Banks in Glasgow and Ogoniland: A Cross‐country Comparison. (4th September 2019) - Okeke‐Ogbuafor, Nwamaka; Gray, Tim
Abstract: In the face of governmental failure across the world to effectively tackle the menace of hunger, this paper explores the perceptions of food bank users in Glasgow in Scotland and Ogoniland in Nigeria's Niger Delta. It relies extensively on qualitative data collected in Glasgow and Ogoniland between 2013 and 2016. Results show that although the concept of food bank is more widespread and established in Glasgow than in Ogoniland, both Glaswegians and Ogonis are increasingly becoming dependent on food banks. In Glasgow, food banks have moved from being last, and short‐term, resorts, to becoming permanent means of alleviating hunger. However, the managers of these food banks are clearly unsure about their long‐term sustainability, and this paper argues that the established model of food bank operating in Glasgow should not be replicated in Ogoniland. Instead, using Freire's concept of 'education for critical consciousness', we suggest an alternative model for food banks that shifts the focus from alleviating hunger to tackling the causes of poverty, that is, a shift from dependency to independency. © 2019 John Wiley & Sons, Ltd.